Maria Blanchard, a woman at the forefront - Monge Zapata, Aitana (Razón y fe, 2018)
In 2012 we commemorated the 80th anniversary of Maria Blanchard’s death, a painter who, despite participating in the avant-garde movements, neither critics nor History of Art recognized the important role she played in the artistic panorama in the early 20th century. Her position as a woman, together with the big malformation she suffered fromwhich marked her whole life was her biggest obstacle to be aprenciated as an artist. Fortunately, whit exhibitions such as those celebrated in Santander and Madrid, this forgotten figure for almost eighty years, is being rediscovered.
Keywords: Maria Blanchard; 20th century avant-gardes; retrospective; Botin-MNCARS foundation